2018
DOI: 10.3389/fonc.2018.00435
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy Combined With Checkpoint Blockade Immunotherapy for Metastatic Undifferentiated Pleomorphic Sarcoma of the Maxillary Sinus With a Complete Response

Abstract: Background: Undifferentiated pleomorphic sarcoma (UPS) of the maxillary sinus is an extremely rare malignancy of the head and neck. Surgery is the mainstay of treatment for UPS; however, proximity to vital structures makes it challenging to achieve negative surgical margins. Adjuvant therapy including radiation therapy with or without chemotherapy is generally indicated. Despite advances in multimodality treatment, objective response rates to available therapies and prognosis of metastatic UPS remain dismal. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…10 14 Several individual case reports have shown that sarcoma patients treated with ICB achieve a positive response or complete remission. [15][16][17][18][19] All patients presented with unique sarcoma subtypes and with varying levels of checkpoint receptor expression, thus identifying commonalities between the positive responses was challenging. The SARC028 (NCT02301039) was one of the first multicenter phase II trials evaluating the effectiveness of ICB in sarcoma.…”
Section: Immune Checkpoint Blockadementioning
confidence: 99%
“…10 14 Several individual case reports have shown that sarcoma patients treated with ICB achieve a positive response or complete remission. [15][16][17][18][19] All patients presented with unique sarcoma subtypes and with varying levels of checkpoint receptor expression, thus identifying commonalities between the positive responses was challenging. The SARC028 (NCT02301039) was one of the first multicenter phase II trials evaluating the effectiveness of ICB in sarcoma.…”
Section: Immune Checkpoint Blockadementioning
confidence: 99%
“…It is known that high PD-L1 expression levels and a high mutational burden are correlated with higher response rates to PD-1-based immunotherapies (8). Previous studies have revealed the effect of combining immunotherapy and radiotherapy on maxillary sinus cancer (8,9) indicating favorable responses. Thus, it may be used as an alternative for this patient if he elected radiotherapy, despite that radiation toxicity must be considered due to the history of the patient with radiotherapy for nasopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies on the use of the combination of chemotherapy and radiotherapy for maxillary sinus cancer investigating the effect of the combination of immunotherapy and radiotherapy on maxillary sinus cancer (8,9). However, to date, no study has investigated the combination of chemotherapy and immunotherapy for maxillary sinus cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, meaningful responses to nivolumab-ipilimumab combination therapy and pembrolizumab therapy have been reported in pretreated UPS [19.20]. The combination of immune checkpoint inhibitors and radiotherapy for UPS that was refractory to conventional chemotherapy achieved complete response (CR) in a case report [21]. Currently, the effects of preoperative radiotherapy and immune checkpoint inhibitor therapy on retroperitoneal UPS are being explored [22].…”
Section: Discussionmentioning
confidence: 99%